Having Good Speaking English through Tik Tok Application - Destia Herlisya; Purna Wiratno (CV. Tripe Konsultan, 2022)
Tik tok is one of the most loved apps in the millennial era. The Tik Tok application is an application to create and share various short videos in vertical format, which is played by simply scrolling the screen up or down. Tik Tok users are increasing every day, especially during the pandemic era. In 2020, as of October Tik Tok reached 2 billion downloads worldwide. This application originating from China is widely downloaded by social media users to relieve boredom when they have to stay at home. This study aims to improve students' speaking skills through the Tik Tok application. The subjects of this study were 20 students of the third semester in English education major at STKIP PGRI Bandar Lampung. The method used is descriptive quantitative method using classroom action research techniques. Based on the result, the improvement of students’ learning activities showed mean score of students’ learning activities in pre cycle is 68.88, in cycle I was 69 with the criteria was less active. While, the mean score of students’ learning activities in cycle II was 76.75 with the criteria were quite active. So, the improvement of students’ learning activities the first cycle to the second cycle was 7.75 point. From analyzing data, it could be concluded that classroom action research by using Tik Tok App improved students’ learning activities and students’ speaking skill.